Extramedullary Plasmacytoma of the Oral Cavity: A Rare Case in the Buccal Mucosa - Armin Khaleghi; Nafise Shamloo (Clinical Case Reports)
ABSTRACT Extramedullary plasmacytomas (EMP) are uncommon solitary tumors composed of neoplastic plasma cells occurring outside the bone. These lesions are of clinical significance due to their potential progression to multiple myeloma (MM), a more systemic and serious plasma cell malignancy. Although EMPs primarily arise in the head and neck region, cases involving the oral cavity are particularly rare. This report presents a case of EMP in a 59‐year‐old Iranian female, who developed a mass on the left buccal mucosa, an atypical site for this type of lesion. The patient presented with a 1‐month history of a painful swelling on her left buccal mucosa. Clinical examination revealed a firm, exophytic lesion with a smooth surface. Histopathological analysis, supported by immunohistochemical staining, confirmed the diagnosis of EMP. The lesion was treated successfully through a combination of surgical excision and radiotherapy at a dose of 40 Gy. This case underscores the importance of early diagnosis and treatment of EMP, particularly in rare locations, to prevent progression to MM and improve patient outcomes. Our findings contribute to the limited body of literature on EMPs in the oral cavity, highlighting the need for awareness of such presentations among clinicians.